2011
DOI: 10.1177/0961000610390992
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pleasure reading in the lives of young teens: Self-identification, self-construction and self-awareness

Abstract: This paper reports on a research study investigating the role of pleasure reading in the lives of 12—15 year old residents of an eastern Canadian regional municipality. Pleasure reading was found to fulfil three broad functions: it enhanced academic performance, social engagement and personal development. In conclusion, the study confirms that teens, like adults, unconsciously use pleasure reading as a means of everyday life information seeking and the reasons for personal salience identified in the foregoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 10 publications
3
47
0
11
Order By: Relevance
“…In such circumstances public libraries (PL) can provide a key information access and support role, but we also know that the use of PL declines dramatically with adolescence, attributed to a disconnect between service provision and service demand (The Reading Agency, 2011, The Reading Agency, 2004, and negative views of libraries and librarians (Agosto and Hughes-Hassell, 2005;Julien, 1999). In relation, recreational reading, which is reported to enhance academic performance, social engagement, and personal development, also declines throughout adolescence (Howard, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In such circumstances public libraries (PL) can provide a key information access and support role, but we also know that the use of PL declines dramatically with adolescence, attributed to a disconnect between service provision and service demand (The Reading Agency, 2011, The Reading Agency, 2004, and negative views of libraries and librarians (Agosto and Hughes-Hassell, 2005;Julien, 1999). In relation, recreational reading, which is reported to enhance academic performance, social engagement, and personal development, also declines throughout adolescence (Howard, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Rosenblatt's (1994Rosenblatt's ( , 1995Rosenblatt's ( , 2005 view, texts and the surrounding context (related activities) must work in tandem to nurture aesthetic transactional reading experiences. Aesthetic transactions afford readers the opportunity to forge meaningful connections with characters and events (Howard, 2011;Rosenblatt, 1995;Strum & Michel, 2009). Readers may learn more about their own lives and experience a sense of comfort and confidence through participation in such moments of textual connectivity (Becnel & Moeller, 2015;Del Nero, 2017;Tatum, 2014;Wilhelm & Smith, 2014a).…”
Section: Personal and Social Learning Through Aesthetic Readingmentioning
confidence: 99%
“…Readers also aesthetically transact through vicarious participation in textual circumstances that contrast to their lives (Del Nero, 2017;Howard, 2011;Lewis, 2000;Rosenblatt, 1995). These aesthetic transactions involve learning through imaginative participation (Dickson & Costigan, 2011;Eisner, 2002;Greene, 2001;Rosenblatt, 1994;Vasudevan, 2010).…”
Section: Personal and Social Learning Through Aesthetic Readingmentioning
confidence: 99%
“…As to the question of where teens access their reading material, reports also vary. Howard's () study, conducted in a Canadian regional municipality, suggests that teens acquire it from home or chain bookstores, whereas Hughes‐Hassell and Rodge, using data gathered from an urban population, reported that teens procure items from the school library, public library, and classroom.…”
Section: Literature Reviewmentioning
confidence: 99%